Melatonin ameliorates diabetic hyperglycaemia-induced impairment of Leydig cell steroidogenic function through activation of SIRT1 pathway - Ping Wang; Shoubing Zhang; Shuai Lin; Zhengmei Lv (BMC, 2022)
Abstract Background Diabetes mellitus (DM)-related complications are important health problems worldwide. The underlying mechanisms for diabetic male subfertility/infertility are considerably complicated and need to be unveiled for therapeutic intervention. Melatonin treatment was investigated to assess the beneficial effects on injured steroidogenic function in DM due to its regulatory roles in mitochondria and autophagy. Methods Diabetic hyperglycaemia was induced in rats injected with streptozotocin (STZ, 55 mg/kg/d) or simulated in TM3 Leydig cell line cultured with medium containing 30 mM D-glucose. Then, diabetic rats or the TM3 cells under high glucose were treated with melatonin. The diabetic rats were randomly divided into diabetes mellitus group (DM group), insulin treatment group (DM + INS group) and melatonin treatment group (DM + MT group). The TM3 Leydig cells were divided into a normal glucose control group (NG group), a high glucose treatment group (HG group), and a melatonin treatment group (HG + MT group). Then, Sirt1 (silent mating type information regulation 2 homologue) 1 expression was knocked down by siRNA. Results The results showed that hyperglycaemia induced a decline in steroidogenesis, accompanied by autophagy defects, mitochondrial dysfunction and oxidative stress, in rats in the DM group or TM3 Leydig cells in the HG group. Furthermore, reduced SIRT1 expression levels and hyperacetylation were found in Leydig cells of DM group. Melatonin treatment ameliorated hyperglycaemia-induced impairment of Leydig cell function with simultaneous stimulation of 5'-adenosine monophosphate activated protein kinase (AMPK)/SIRT1 activity and the expression of autophagy-related genes. With regards to mitochondrial function, it promoted mitochondrial biogenesis with elevated PGC-1α, NRF1 and mtTFA, improved mitochondrial morphology, increased BNIP3L-related mitophagy and alleviated oxidative stress. Further results revealed that knockdown of Sirt1 in Leydig cells prevented the protective effects provided by melatonin against high glucose treatment, and interestingly, neutralization of reactive oxygen species (ROS) by N-acetyl-L-cysteine pretreatment abolished the stimulatory effect of melatonin on AMPK/SIRT1 activity in Leydig cells and prevented the induction of autophagy and mitochondrial biogenesis in the context of high glucose, indicating that modulation of SIRT1 pathway by melatonin was closely linked to ROS levels and oxidative stress. Conclusions These findings suggest that SIRT1 pathway plays essential roles in the pleiotropic actions of melatonin on Leydig cells and in the prevention of hyperglycaemia-induced steroidogenic dysfunction. The stimulatory action of melatonin on SIRT1 pathway is related to oxidative stress and its antioxidant property. Our data provide new evidence for the relationship of melatonin and SIRT1 pathway in the context of hyperglycaemia, and melatonin as a combination therapy may be useful to combat DM-related complications, especially male reproductive system injury.